Avatar embodiment in VR: Are there individual susceptibilities to visuo-tactile or cardio-visual stimulations? - Pratviel, Yvan; Bouni, Alix; Deschodt-Arsac, Véronique; Larrue, Florian; Arsac, Laurent M. (Frontiers in Virtual Reality, 2022)
Virtual reality has obvious potential to help humans developing/recovering brain functions which operate through multisensory inputs modulations. Some interventions using VR rely on the need to embody a virtual body (avatar). Embodiment can be facilitated by synchronizing natural sensory inputs with their visual redundancy in VR, e.g the heartbeat flashing around the avatar (cardio-visual illusion) or body touch felt and seen (visuo-tactile illusion). While these so-called Full-Body Illusions have proven obvious interest in health and disease, it is unknown whether a same individual has equivalent sensitivity to either cardio-visual or visuo-tactile stimulations, and what individual dispositions may interfere with this processing. Here, twenty-nine young and healthy participants underwent an experiment twice, with both cardio-visual and visuo-tactile stimulations to induce the full-body illusion. The effect of synchronous stimulations on three components of the bodily self-consciousness (self-location, perspective taking and self-identification) were studied comparatively using non-declarative tasks. The type of stimulation (cardio-visual or visuo-tactile) had no significant effect on the evolution of these components following the illusion. Moreover, a principal component analysis demonstrated the lack of covariation between those components, pointing to the relative independence of self-location, perspective taking and self-identification measurements. Based on psychological and cognitive measurements prior to the task, no particular profile suggesting individual predispositions to a certain type of multisensory stimulation emerged. In conclusion, visuo-tactile and cardio-visual stimulations induce similar changes in three components of bodily self-consciousness, which appear to be relatively independent from each other.